Rancang Bangun Mesin Penggorengan Chicken Dengan Metode Deep Fryer - Jaelani; Muhamad Zainudin; Laelatul Fatimah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research aims to design and develop a specialized frying device for chicken using the deep fryer method. The deep frying method was chosen for its ability to produce a crispy texture and even cooking. The design process of this device involves user needs analysis, mechanical design, and prototype testing. The developed frying device is designed to improve efficiency and consistency in the chicken frying process, as well as to minimize oil absorption in the final product. The test results show that this device is capable of producing chicken with optimal texture and taste. The use of this device is expected to be a practical solution for the culinary industry in enhancing the quality and efficiency of the chicken frying process. Data collection was conducted through observation, documentation, and literature study. The data analysis used was descriptive. After the design process, testing of the device was carried out to determine the doneness of the chicken using cooking times of 8 minutes, 14 minutes, and 20 minutes. The research results showed that the design process was carried out through several stages of component design. The test results indicated that frying for 14 minutes was the most optimal for producing perfectly cooked chicken with a crispy exterior, tender interior, and balanced flavor.